121k views
2 votes
Find the inverse of h(x)=(2x-4)/3

User Dothebart
by
5.7k points

2 Answers

5 votes

Answer:

H^-1 (x)= 3x+4/2

Explanation:

Took the test

User Amar Pratap
by
6.0k points
2 votes

Answer:

The inverse of the h(x) is
h^(-1)(x)=(3x)/(2)+2 Explanation:

Given : Expression
h(x)=(2x-4)/(3)

To find : The inverse of the expression ?

Solution :

Expression
h(x)=(2x-4)/(3)

Let, h(x)=y then
y=(2x-4)/(3)

For inverse we replace the value of x and y and find the value of y in terms of x.

Replace the value of x and y,


x=(2y-4)/(3)

Solve for y by cross multiply,


3x=2y-4

Adding 4 both side,


3x+4=2y

Dividing by 2 both side,


(3x+4)/(2)=y

Therefore, The inverse of the h(x) is
h^(-1)(x)=(3x)/(2)+2

User Chojnicki
by
5.3k points